Conjugate natural convection in a nanofluid filled partitioned horizontal annulus formed by two isothermal cylinder surfaces under magnetic field - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2017)
Natural convection in a CuO-water nanofluid filled horizontal partitioned annulus formed by two isothermal surfaces under the influence of an inclined magnetic field was numerically investigated. A conductive partition with varying thickness and thermal conductivity was placed within the annulus. Finite element method was utilized to solve the governing equations. The influence of the Rayleigh number (between 10(4) and 10(6)), Hartmann number (between 0 and 40), magnetic inclination angle (between 0 degrees and 90 degrees), thermal conductivity of the partition (between 0.06 and 60) and solid volume fraction of the nanoparticle (between 0 and 0.04) on the fluid flow and heat transfer characteristics were studied for various thickness values of the partition. Local and average Nusselt number along the inner surface enhance as the value of the thickness of the partition and Rayleigh number and magnetic inclination angle (up 45 degrees) increase and as the value of Hartmann number decreases. The influence of the thickness of the conductive partition is more pronounced in the conduction dominated regime when Rayleigh number is low and Harttnann number is high. Average heat transfer enhances with thermal conductivity of the partition and this is more effective for a thicker partition. Almost a linearly varying relation exists between the average Nusselt number and solid nanoparticle volume fraction and the slope of the curve is slightly higher for a thick partition. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Conjugate natural convection; Partitioned annulus; Magneto-hydrodynamics; Nanofluid; Finite element method